COCONUT NUTRITION IN PAPUA NEW GUINEA - Ollivier, J; Akus, W.; X. Bonneau (International Coconut Community, 1999)
Copra yield in Papua New Guinea is estimated at 0.6 tonnes per hectare per year. Several factors may be responsible for this low productivity compared to other Asia Pacific countries. Amongst these, nutrient deficiency is an important limiting factor. In order to evaluate coconut nutrition status in PNG, leaf sample collection was undertaken by examining 23 sites around the country and from a nutrition trial carried out at the Stewart Research Station of the PNG Cocoa & Coconut Research Institute (PNG-CCRI) in the Madang Province. Results of leaf analysis revealed significant widespread nitrogen deficiencies at most of the sampled sites and geographic variations in potash deficiency. Chlorine deficiency varied with geographic sites and was closely related to the prevailing wind pattern. Preliminary results on nut-set and flowering in the trial at Stewart Research Station revealed a positive response to nitrogen and chlorine-based fertilizer applications. This suggests that appropriate fertilizer applications would be benefit future coconut production on this particular site.